2019
DOI: 10.1136/esmoopen-2018-000470
|View full text |Cite
|
Sign up to set email alerts
|

Assessing molecular subtypes of gastric cancer: microsatellite unstable and Epstein-Barr virus subtypes. Methods for detection and clinical and pathological implications

Abstract: BackgroundThe molecular classification of gastric cancer recognises two subtypes prone to immune checkpoint blockade: the microsatellite unstable and the Epstein-Barr virus (EBV)-related tumours. We aim to assess the concordance between immunohistochemistry and PCR for microsatellite status evaluation, and explore the value of microsatellite instability (MSI) and EBV as predictive survival factors.Material and methodsWe collected 246 consecutively diagnosed gastric cancer cases in all stages and evaluated the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
27
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(34 citation statements)
references
References 47 publications
7
27
0
Order By: Relevance
“…The incidence of MMR deficiency among AN patients is 10%, similar to Asians [57], and lower than the 22% that has been observed in Western populations, 22% [13,58,59]. A positive association was observed between MMR deficiency and patients who are female, over the age of 50, have an SNV mutation, and cancer in the distal stomach, consistent with the studies analyzing MMR deficiency with clinicopathological factors [60,61]. We, however, did not observe a correlation with subtype, which has been observed in some studies [57,62], but not others [58,59].…”
Section: Discussionsupporting
confidence: 85%
“…The incidence of MMR deficiency among AN patients is 10%, similar to Asians [57], and lower than the 22% that has been observed in Western populations, 22% [13,58,59]. A positive association was observed between MMR deficiency and patients who are female, over the age of 50, have an SNV mutation, and cancer in the distal stomach, consistent with the studies analyzing MMR deficiency with clinicopathological factors [60,61]. We, however, did not observe a correlation with subtype, which has been observed in some studies [57,62], but not others [58,59].…”
Section: Discussionsupporting
confidence: 85%
“…In the present study, the MSI type accounted for ~21.5% of all GC cases, was diagnosed at relatively older ages and was more common in females. Previous studies have shown that the majority of patients with MSI type exhibited intestinal-type GC predominantly located in the distal stomach; the majority of these patients were female and displayed an association with age (5,13,14). In the present study, sequencing revealed that the mutation rate of ARID1A and CDH1 were 21.5 and 3.1%, respectively.…”
Section: Discussionsupporting
confidence: 52%
“…In the present study, the estimated EBV positive rate was 11.3%. EBV positive rates ranged from 1.2% to 89.2% in the individual eligible studies [ 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , …”
Section: Discussionmentioning
confidence: 99%